2019
DOI: 10.1080/13811118.2019.1574689
|View full text |Cite
|
Sign up to set email alerts
|

Nexus of despair: A network analysis of suicidal ideation among veterans

Abstract: Objective-To estimate a network model of risk and resilience factors of suicidal ideation among veterans.Methods-Two network models of suicidal ideation among OIF/OEF/OND veterans (N = 276) incorporated key disorders, traumatic stress, and resilience constructs to contextualize suicidal ideation.Results-Childhood trauma was positively connected with suicidal ideation and harassment and inversely connected with social support and distress tolerance. This exemplifies long-lasting associations between childhood t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 90 publications
1
14
0
Order By: Relevance
“…The association between suicidal ideation and depression was the strongest of these relationships, with a moderate positive correlation estimated between these variables. In previous suicide network research , Simons et al (2019) resilience, which the results of the present study support. Furthermore, a number of nonnetwork studies report similar findings to the present study, with negative relationships between suicidality and self-esteem (Fergusson et al, 2003;Thompson & Light, 2011), access to mental health services (Reynders et al, 2015;Stanley et al, 2016), and positive attitude towards mental health services (Stanley et al, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…The association between suicidal ideation and depression was the strongest of these relationships, with a moderate positive correlation estimated between these variables. In previous suicide network research , Simons et al (2019) resilience, which the results of the present study support. Furthermore, a number of nonnetwork studies report similar findings to the present study, with negative relationships between suicidality and self-esteem (Fergusson et al, 2003;Thompson & Light, 2011), access to mental health services (Reynders et al, 2015;Stanley et al, 2016), and positive attitude towards mental health services (Stanley et al, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…The association between suicidal ideation and depression was the strongest of these relationships, with a moderate positive correlation estimated between these variables. In previous suicide network research, Simons et al (2019) andDe Beurs et al (2019) reported a positive association between suicidal ideation and depression or depressive symptoms. Additionally, De Beurs et al (2019) reported an association between suicidal ideation and both perceived burdensomeness and resilience, which the results of the present study support.…”
Section: Discussionmentioning
confidence: 87%
“…One of the fast-expanding research fields focused on identifying associations between a wide array of symptoms and other factors, and commonly utilizing network models, is the field of post-traumatic stress. Over the past half-decade, numerous studies investigating associations between symptomatology (Mcnally et al, 2015;van Loo et al, 2018), potential risk factors (Armour et al, 2017;Choi et al, 2017;Mancini et al, 2019;Simons et al, 2019) and pathways to comorbidity (Djelantik et al, 2020;Gilbar, 2020;Lazarov et al, 2019;Malgaroli et al, 2018;Price et al, 2019;Vanzhula et al, 2019) have been published and yielded novel results and hypotheses. In response to this rapid research expansion and in an aim to synthesize current findings in the field, a thorough systematic review of the network approach to posttraumatic stress disorder (PTSD) has been recently carried out (Birkeland et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%